Bleaching of Xylanase-Treated Bamboo Fibre with Eco-Enzyme Assisted Power Ultrasonic - Mohd Fauzi, Mohd Sufi Huzaimi; Che Pa, Ts. Dr. Nasrul Fikry (Progress in Engineering Application and Technology, 2022)
This study ventured to determine the effectiveness of eco-enzyme bleaching treatment towards xylanase-treated bamboo fibre with the assisted of power ultrasonic since the conventional bleaching treatment produced toxic effluent which will affect the human health. This study aims to synthesis bamboo fibre from Schizostachyum grande (Semeliang) type of bamboo via bamboo fibre extraction machine, determine eco-enzyme bleaching treatment towards xylanase-treated bamboo fibre assisted power ultrasonic at different pre-treatment conditions temperature (40°C, 60°C and 80°C) and processing time (60 min, 90 min, 120 min), and analyse tensile strength via INSTRON 50 kN Blue Hill 3369 Universal Testing Machine (UTM) and brightness of bleaching treated bamboo fibre via HunterLab Colorimeter. The result revealed that soft Schizostachyum grande fibre were easily produced via bamboo fibre extraction machine. Tensile strength shows an increasing trend with the highest value of 553.44 MPa for xylanase-treated bamboo fibre at 80°C for 60 min. Bamboo fibre treated with eco enzyme shows decreasing trend with the highest tensile strength value of 400.66 MPa at 35°C for 60 min. The brightness of xylanase-treated bamboo fibre with low concentration eco-enzyme having highest value of 73.66 compared to higher concentration eco-enzyme treated bamboo fibre (74.46) suspected due to the cavitation effects produced by ultrasonic that increased the diffusity and mass transfer rate of xylanase and eco-enzyme into the fibre. This findings can be set as a benchmark of an effective method to bleach bamboo fibre assisted power ultrasonic and xylanase enzyme instead of using hydrogen peroxide that affected the environment and human being.